Students’ Adaptation in the New School - Rupšienė, Liudmila; Kučinskienė, Ramutė (Acta Paedagogica Vilnensia, 2006)
In 2004 by request of the Ministry of education and science of Lithuania we conducted the first nation scale research "Quality of education at different types of schools: attitude of children transitioned from one school to another and their parents", orientated precisely at the school transition problems. This article presents a part of this research results. In this article we aimed to reveal how students’ adaptation after a school transition is related to teachers’ behaviour.